Stratégie alimentaire des coquelets en zone tropicale: Ration complète comparée au système cafétéria - CHRYSOSTOME, CHRISTOPHE ACHILLE A. MAHUSSI; HOUNDONOUGBO, M. FRÉDÉRIC; KPOMASSE, C. Claude (My University, 2010)
An experiment was carried out to evaluate the feeding system effect on bio-economic performances of cockerels in tropical region. 150 day old ISA Brown cockerels were split in six repetitions of 25 chicks each. Chicks were kept respectively during height and six weeks at starter and grower phases. Three repetitions were fed with a complete diet (Ro), and the three other were fed by the cafeteria feeding system (Rc). Three separate feeders providing mainly energy, protein and mineral plus vitamin constituted the Rc diet. The results demonstrate that the feed intake and specifically, metabolisable energy intake of Rc cockerels were higher than that of Ro cockerels. The protein intake of Rc cockerels was lower than that of Ro cockerels. The intake of mineral and vitamin had varied according to the feeding system and the phase. However, the feeding system had no significant effect (P > 0.05) on the body weight gain, feed conversion ratio, feed cost and economic feed efficiency. At 14 weeks old, the average body weights of Ro and Rc cockerels were similar (1311 versus 1214 g). Feed conversion ratio, feed cost and economic feed efficiency in Ro and Rc diets were respectively 5.12 versus 5.52 kg feed/kg weight gain, 1163 versus 1184 FCFA feed / kg weight gain and 1.60 versus 1.48 FCFA feed / FCFA weight gain. No mortality was recorded in both dietary treatments.
Keywords: Benin; efficiency of feeding system; nutrients and energy intake